2016
DOI: 10.1177/1038416216658774
|View full text |Cite
|
Sign up to set email alerts
|

Employability skills for entry-level human resources management positions: Perceptions of students and employers

Abstract: This paper offers (a) a multidimensional Employability Skill Scale development method, and (b) one 30-item, seven-dimensional, and another 26-item six-dimensional employability skill requirement scale for use with entry-level human resources management positions, as perceived by employers and students, respectively, in Bangladesh. The study is based on samples of 174 and 446 survey responses collected from corporate managers and university students, respectively. There were significant variations in opinions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Managers also suggested that presentation ability, mainly verbal communication, is another important skill they would like to see among the candidates. A quick look at the skills with higher priority (shaded ones in Table 6) shows that Bangladeshi companies put more emphasis on "Academic Skills" while recruiting entry-level executives (also reported in Chowdhury & Miah, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers also suggested that presentation ability, mainly verbal communication, is another important skill they would like to see among the candidates. A quick look at the skills with higher priority (shaded ones in Table 6) shows that Bangladeshi companies put more emphasis on "Academic Skills" while recruiting entry-level executives (also reported in Chowdhury & Miah, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare an initial pool of skill items, the authors sorted out all available employability attributes irrespective of the country of study and job categories (similar approach followed by Chowdhury & Miah, 2016). This initial list then can be customized to the priorities of the employers (both local and MNCs) of Bangladesh through a three-step process-refining with academic experts, further purification with human resource (HR) managers and by using quantitative data (please refer to Research Method section).…”
Section: Conceptualizing Employability Skillsmentioning
confidence: 99%
“…Peers encouraging each other highlight potential for academics to use PPSI for countering student's minimalist approach with reading learning materials [41]. Moreover, peer to peer interaction provided an avenue for students to practice workplace-relevant skills such as team-building capability [33]. Additionally, this study endorsed interrelation between PPSI induced student's engagement with reading materials and workplace relevant learning.…”
Section: Discussionmentioning
confidence: 55%
“…This implies that academics will be rewarded with a stronger enhancement of student engagement when delivering teaching interventions that facilitate both academic learning and workplace relevant cognition. Given that employers in Bangladesh are looking for subject knowledge as well as knowledge application [31,33], this type of teaching intervention is necessary to improve quality in higher education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation